15-Deoxy-γ12, 14-prostaglandin J2 Reduces Liver Impairment in a Model of ConA-Induced Acute Hepatic Inflammation by Activation of PPARγ and Reduction in NF-κB Activity. (10th July 2014) - Chen, Kan; Li, Jingjing; Wang, Junshan; Xia, Yujing; Dai, Weiqi; Wang, Fan; Shen, Miao; Cheng, Ping; Zhang, Yan; Wang, Chengfen; Yang, Jing; Zhu, Rong; et al.
Abstract : Objective . 15-Deoxy-Δ12, 14-prostaglandin J2 (15d-PGJ2) reduces inflammation and has been identified as an anti-inflammatory prostaglandin in numerous animal models. In this study, we investigated both effects of 15d-PGJ2 and its protection mechanism in concanavalin A- (ConA-) induced autoimmune hepatitis in mice. Materials and Methods . In vivo, Balb/C mice were injected with ConA (25 mg/kg) to induce acute autoimmune hepatitis, and 15d-PGJ2 (10 μ g or 25 μ g) was administered 1 h before the ConA injection. The histological grade, proinflammatory cytokine levels, and NF- κ B and PPAR γ activity were determined 6, 12, and 24 h after the ConA injection. In vitro, LO2 cells and RAW264.7 cells were pretreated with 15d-PGJ2 (2 μ M) 1 h before the stimulation with ConA (30 μ g/mL). The NF- κ B and PPAR γ activity were determined 30 min after the ConA administration. Results . Pretreatment with 15d-PGJ2 reduced the pathological effects of ConA-induced autoimmune hepatitis and significantly reduced the levels of cytokines after injection. 15d-PGJ2 activated PPAR γ, blocked the degradation of I κ B α, and inhibited the translocation of NF- κ B into the nucleus. Conclusion . These results indicate that 15d-PGJ2 protects against ConA-induced autoimmune hepatitis by reducing proinflammatory cytokines. This reduction in inflammation may correlate with the activation of PPAR γ and the reduction in NF- κ B activity.